2015
DOI: 10.1063/1.4919428
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism insight into the effect of I/P buffer layer on the performance of NIP-type hydrogenated microcrystalline silicon solar cells

Abstract: A simulation and experimental study on the effect of the buffer layer at the I/P interface on the performance of NIP-type hydrogenated microcrystalline silicon (lc-Si:H) single-junction solar cells is presented. Device-quality hydrogenated amorphous silicon (a-Si:H) material as a buffer layer at the I/P interface obviously improves the performance of NIP-type lc-Si:H single-junction solar cells. In addition to the well-known mechanism that an a-Si:H I/P buffer layer can reduce the recombination current density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…To ensure the effect of HTMs for enhancing R P , a comparison of defect density between samples was carried out by analyzing biased EQE spectra and dark J–V curves. As the defect density is closely correlated with R P , fewer defects result in R P enhancements. , In addition to increasing R P , collecting EQE spectra at reverse bias voltages made it possible to distinguish collection losses from optical losses. In p-i-n-type solar cells, the comparison of EQE (Figure S3a) at a given wavelength, with the corresponding EQE under reverse bias, enables differentiation between collection losses and optical losses, as shown in Figure S3b.…”
Section: Introductionmentioning
confidence: 99%
“…To ensure the effect of HTMs for enhancing R P , a comparison of defect density between samples was carried out by analyzing biased EQE spectra and dark J–V curves. As the defect density is closely correlated with R P , fewer defects result in R P enhancements. , In addition to increasing R P , collecting EQE spectra at reverse bias voltages made it possible to distinguish collection losses from optical losses. In p-i-n-type solar cells, the comparison of EQE (Figure S3a) at a given wavelength, with the corresponding EQE under reverse bias, enables differentiation between collection losses and optical losses, as shown in Figure S3b.…”
Section: Introductionmentioning
confidence: 99%
“…Interface defects at n/i and i/p layers limit optical and electrical transport in the solar cell. Zhang et al [14], Mews et al [15], Agbo et al [16], Bai et al [17] and Xiao et al [18], reported that these interface defects can be minimized by the exposure of H 2 plasma treatment (HPT) at the interfaces. The performance of other solar cells, like perovskite based solar cells is also controlled by the interfaces between different layers and can be significantly improved by interface modifications as reported by Lim et al [19,20].…”
Section: Introductionmentioning
confidence: 99%